In vitro Antifungal Susceptibility of Agents for Superficial Phaeohyphomycosis - Viviane Pagnussat; Gabriella da Rosa Monte Machado; Janaína Scarton; Alexandre Meneghello Fuentefria (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
The selection of fungal isolates resistant to available therapy associated with an increase in the number of immunosuppressed patients has contributed to the incidence of infections caused by dematiaceous fungi. Thus, this study evaluated the therapeutic efficacy of the main antifungal agents currently used in clinical practice in relation to Curvularia spp. and Hortaea werneckii from cases of superficial phaeohyphomycosis from southern Brazil. The susceptibility profile of amphotericin B, fluconazole, itraconazole, terbinafine and voriconazole against dematiaceous fungi (Curvularia lunata, C. pallescens and H. werneckii) was evaluated by microdilution in broth. Terbinafine showed greater efficacy against C. lunata - gemometric mean (GM = 0.38 μg/mL), C. pallescens (MIC = 0.125 μg/mL) and H. werneckii (GM = 0.031 μg/mL) when compared to the other antifungals tested. Most of species showed sensitivity to itraconazole and voriconazole, with a minimum inhibitory concentration (MIC) range from 1 - 8.0 μg/mL and 0.5 - 2.0 μg/mL, respectively. All isolates tested show low sensitivity to fluconazole (MIC range 4 - 16 μg/mL). Although itraconazole is considered gold standard, terbinafine has been showed to be a good alternative for the treatment of superficial phaeohyphomycosis. Lastly, antifungal susceptibility testing is essential to indicate the ideal therapy against these infections.